2018
DOI: 10.1111/hdi.12642
|View full text |Cite
|
Sign up to set email alerts
|

Postdialysis recovery time is extended in patients with greater self‐reported depression screening questionnaire scores

Abstract: Prolonged postdialysis recovery times are associated with higher self-reported depression scores, and very low postdialysis blood pressure. Future studies investigating changes in dialysis practice and recovery times will need to target strategies to prevent intradialytic hypotension and adjust for patient psychological status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 30 publications
6
40
3
3
Order By: Relevance
“…14 It is likely that differences in dialysis treatments may affect early recovery, whereas longer recovery times patients reflect general fatigue. 30 Haemodynamic factors may also play a major role in the differences in short term survival we have described. Ultrafiltration during HD may result in reduced organ perfusion during which may have detrimental consequences such as reduced blood to the heart leading to cardiac stunning, 31 and to the brain 32 which may increase cognitive decline, 33 and postdialysis hypotension which is reported to reduce patient survival.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…14 It is likely that differences in dialysis treatments may affect early recovery, whereas longer recovery times patients reflect general fatigue. 30 Haemodynamic factors may also play a major role in the differences in short term survival we have described. Ultrafiltration during HD may result in reduced organ perfusion during which may have detrimental consequences such as reduced blood to the heart leading to cardiac stunning, 31 and to the brain 32 which may increase cognitive decline, 33 and postdialysis hypotension which is reported to reduce patient survival.…”
Section: Discussionmentioning
confidence: 87%
“…The BDI‐II questionnaire contains a number of questions related to fatigue, and fatigue is commonly reported by dialysis patients, and this overlap may well account for the difference between the higher prevalence of self‐reported depression using screening questionnaires such as the BDI‐II and the much lower prevalence reported when patients are formally reviewed by psychiatrists . It is likely that differences in dialysis treatments may affect early recovery, whereas longer recovery times patients reflect general fatigue …”
Section: Discussionmentioning
confidence: 99%
“…Dialysis symptoms have variously been ascribed to the rapid reduction in plasma osmolality [3,5] and the reduction in effective circulating plasma volume [7,9,15]. However, with technological improvements in the dialysis machines and dialysis water quality [1], more recently, reports have suggested that other factors, in terms of patient demographics and co-morbidity, and in particular psychosocial well-being have a greater influence on self-reported dialysis symptoms [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a significant association between the distress thermometer scores and both dialysis symptom scores and the time taken to recover post-dialysis. Other studies have also observed an effect of patient psychological distress on self-reported depression and the time to recovery after dialysis [15][16][17]. Previous studies have reported an association between longer post-dialysis recovery times and a history of psychiatric disorders, in particular depression [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation